What constitutes the surface approach to learning in the light of new empirical evidence? - Sari Lindblom-Ylänne; Anna Parpala; Liisa Postareff (Routledge, 2022)
This study aims, firstly, to examine the nature of the surface approach to learning in today’s university context, and secondly, to explore the factors that explain variations in the use of this approach. The 61 participants were studying in six Bachelor programmes representing various disciplines. These students scored above average on a surface approach scale and volunteered to be interviewed. One compulsory course was selected from each programme. Five surface approach profiles emerged showing variation from a full surface approach to a deep approach with memorisation. Despite very similar high scores on the surface approach scale, students varied in their use of surface-level processes. Thus, the inventory data did not capture the full variation in the students’ use of the surface approach to learning. Rich research methods are therefore needed to better understand the nature of students’ personal aims as well as their study processes and practices.